2021
DOI: 10.21203/rs.3.rs-214352/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Human 3D neural assembloid model for SARS-CoV-2 infection

Abstract: Clinical evidence suggests the central nervous system (CNS) is frequently impacted by SARS-CoV-2 infection, either directly or indirectly, although mechanisms remain unclear. Pericytes are perivascular cells within the brain that are proposed as SARS-CoV-2 infection points1. Here we show that pericyte-like cells (PLCs), when integrated into a cortical organoid, are capable of infection with authentic SARS-CoV-2. Prior to infection, PLCs elicited astrocytic maturation and production of basement membrane compone… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…They found that SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) gene copies in the supernatant increased over time, suggesting that the infected cells could release viral particles ( Zhang and others 2020 ). Similarly, Song and others (2020) , Tiwari and others (2021) , and Gleeson and others (2021) showed evidence of SARS-CoV-2 replication in a brain organoid. Furthermore, viral particles and regions of budding from endoplasmic reticulum-like structures were observed in the organoids using electron microscopy, suggesting that SARS-CoV-2 could even replicate within neurons ( Song and others 2020 ).…”
Section: Sars-cov-2 Neurotropismmentioning
confidence: 84%
See 2 more Smart Citations
“…They found that SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) gene copies in the supernatant increased over time, suggesting that the infected cells could release viral particles ( Zhang and others 2020 ). Similarly, Song and others (2020) , Tiwari and others (2021) , and Gleeson and others (2021) showed evidence of SARS-CoV-2 replication in a brain organoid. Furthermore, viral particles and regions of budding from endoplasmic reticulum-like structures were observed in the organoids using electron microscopy, suggesting that SARS-CoV-2 could even replicate within neurons ( Song and others 2020 ).…”
Section: Sars-cov-2 Neurotropismmentioning
confidence: 84%
“…It has been shown that cerebral organoids are able to form complex brain architectures spontaneously using intrinsic signals ( Benito-Kwiecinski and Lancaster 2020 ). The remaining five studies employed a variety of patterning factors and media that promoted regional specificity of brain organoids like the forebrain, midbrain, hippocampus and hypothalamus organoids ( Gleeson and others 2021 ; Jacob and others 2020 ; Ramani and others 2020 ; Yi and others 2020 ; Zhang and others 2020 ). Particularly, the generation of choroid plexus containing organoids was interesting given that there were two recent studies that highlighted significant susceptibility of the choroid plexus organoid (CPO) to SARS-CoV-2 ( Jacob and others 2020 ; Pellegrini and others 2020 ).…”
Section: Sars-cov-2 Neurotropismmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the combination of microglia-like cells and cortical organoids was previously used to model certain aspects of Alzheimer’s disease [ 144 ]. Furthermore, the introduction of pericyte-like cells enabled the successful infection of cortical organoids with SARS-CoV-2 [ 145 ]. The introduction of immune cells to organoids is especially highly desired in logical and immunological research.…”
Section: Complex In Vitro Models In Viral Researchmentioning
confidence: 99%
“…In addition, researches demonstrated that ACE2 is also expressed in pericytes, another apart of mural cells of the central nervous system (CNS). SARS-CoV-2 may directly destroy pericyte and further reduce blood supply to the brain, and ultimately result in neuronal dysfunction [90,91]. Pericytes are perivascular cells within the brain that are proposed as SARS-CoV-2 infection points [92].…”
Section: Covid-19 On Nervous Systemmentioning
confidence: 99%